Cyclopoid copepods associated with asteroid echinoderms in New Caledonia - Humes, Arthur G. (Washington, D.C. Smithsonian Institution Press, 1976)
Smithsonian contributions to zoology; no. 217
Keywords: Echinodermata--New Caledonia; Crustacea--New Caledonia; Starfishes--New Caledonia; Cyclopoida--New Caledonia